Pedagogical and Psychological Characteristics of the Development of Ability and Talent in Students (Journal of Pedagogical Inventions and Practices, 2023)
This article describes various methods of selecting talented students and working with them effectively in educational institutions. The talent visible in young people is manifested in a great variety, and the rarer it is, the more unique, unrepeatable features, as well as the inner spiritual world of young people is directly external in the formation of a rich, intelligent person. information about the great role of the spiritual environment is given.